Applying lean principles to identify waste in design user interface design / Mohd Fadzly Ismail - Ismail, Mohd Fadzly (2009)
There is an increasing demand for building application involves the design of both data model and a graphical user interface (GUI) to present that model that matches real user needs in working environments. This research tries to apply a quality concept derived from manufacturing known as Lean Thinking into the study of user interface design. The objectives of this research are to define the meaning of waste in the user interface design and to categorize type of waste user in user interface design. To fulfill this objective, evaluation on the current approach and Literature Review has been made. Based on the evaluation and Literature Review, it is known that the main problem is in finding out the meaning of the waste and type of waste in User Interface Design. Thus, this research is to applying Lean Principles which can help to identify the type of waste which can add value in User Interface Design process. This research can contribute a significantly to the user interface developer and user.